Tax Mobilization in Sub-Saharan Africa: The Impact of Tax and Business Law Reforms - Bertinelli, Luisito; Bourgain, Arnaud (Economics Bulletin, 2016)
This paper contributes to measuring the influence of business (and tax) law reforms on sub-Saharan African countries tax mobilization ability. Relying on a new business law reform indicator, our results validate the significant impact of corporate law modernization on governmental revenue, and unearth a complementary effect between business and tax law reforms.

Sovereign wealth funds in international economic law - Dekastros, Michail (European University Institute, 2016)
Sovereign Wealth Funds have been the new 'rising star' of the global economy for a few years. Host States have reacted to their rise cautiously and have quite frequently cited 'national security' as a justification for maintaining an absolute degree of freedom in regulating their entry into their markets. This thesis is arguing that a substantial proportion of regulatory concerns that surround the operation of SWFs are actually not of a national security nature—at least as perceived by the relevant instruments regulating investment in International Economic Law. As a consequence, the current regulatory framework screening SWFs investments a priori is both legally and normatively problematic and, in fact, it constitutes a form of protectionism. As an alternative, this thesis suggests that SWFs ought to be primarily regulated after their entry into Host States' markets. In that context, a proper conceptualisation of the principle of non-discrimination that takes into account the 'regulatory unlikeness' between SWFs and other market suppliers/investors will allow the Host States to properly regulate them after their entry into their markets. Such a conceptualisation – contrary to usual analyses – draws heavily from International Investment law in order to interpret the relevant provisions of the GATS.
Keywords: Foreign investment; International law; Sovereign wealth funds

Assessment of Compliance with OHADA Uniform Accounting Act by Public Limited Companies - Fossung, Michael Forzeh (Accounting and Finance Research, 2016)
Francophone African countries have made a tremendous effort in harmonising domestic standards and reporting with the International Financial Reporting Standards (IFRS). Moving from two distinct OCAM streams to two OHADA streams (effective 1985) and now one OHADA Uniform Accounting Act embodying 17 member countries (effective 2001) is a milestone towards harmonisation of reporting practice both domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards has resulted in the successful convergence of firms' accounting practices by analysing public limited liability companies' compliance with the OHADA Uniform Accounting Act and if such compliance has improved over time. The study has been carried out using the 2008 and 2009 annual reports of three public limited companies in the OHADA zone that translate their financial statements into IFRS. The ranks of closeness and compliance index have been used to analyse data. Findings reveal a relatively high level of compliance with the accounting regulation by sampling limited liability companies. The results also give an indication of harmonisation in accounting practice of limited companies within member countries as they were found to be substantially consistent in compliance, especially in countries that have instituted the Statistics and Tax returns (or "DSF") as a reporting medium.
Number: 3

Reflections on the Nexus Between Public Procurement Reforms and Economic Development in Nigeria - Okolie, Aloysius-Michaels; Nnamani, Kelechi (African Journal of Politics and Administrative Studies, 2016)
Corruption has widely been recognized as one of the impediments to the socio-economic cum political development of Nigeria. By 2000, it was observed that the conduct of government business in Nigeria had become difficult and expensive due to pervasive corruption, particularly procurement fraud. Although procurement fraud is one of the most common avenues of corruption in most countries, its incidence in Nigeria by 2000 was particularly widespread. To reverse this ugly trend, the Nigerian government initiated the public procurement reforms with a view that a corrupt-free procurement process will among other things, promote economic development in the country. Consequent upon the reform, the Public Procurement Act was enacted while the Bureau of Public Procurement was established to ensure due process, accountability and transparency in the award of government contract. In this light, this study evaluated the impact of the public procurement reforms on the economic development of Nigeria. We relied on documentary method of data collection and content analysis of data. Meanwhile, employing the basic propositions emanating from the Marxist theory of the Post-Colonial State, this study noted that the nature and character of Nigerian state undermined the procurement reform from achieving its expected goals. We however, recommended for the removal of the immunity in the constitution and strengthening of the anti-graft agencies in Nigeria.
Keywords: Corruption; Economic Development; Public Procurement; Reforms; Transparency

The Quality of External Audit in OHADA Space: A Qualitative Study with Board of Director’s Members’ Perception as Understanding Variable - Hanko, Osée (Applied Finance and Accounting, 2016)
Audit quality has been evaluated in academic literature accordingly with auditor qualities, due to the difficulties of observing auditing technical process itself. The qualities of a good auditor are then competence and independence, sine qua none conditions of audit quality. That approach is otherwise valid only if there is a valuable framework like stock market where auditor’s competence and independence could be observed. In OHADA space countries, the financial market is approximately off. It is therefore impossible to assess audit quality the way it has been done in prior literature. This study suggests a new approach of assessing audit quality in OHADA countries in relation with audit committees member’s perception of auditing process. Using an innovative qualitative approach inspired from Manita (2008), the results suggest to take into account the auditor’s knowledge of the company, the relevance of the identified zone of risks and the degree of communication with the board of directors.
Number: 2

An investigation into customer accounting in customer-focused organisations - Bates, Ken (Victoria University of Wellington, 2016)
Management accounting information should aid management in the design and implementation of strategy. Firms adopting a customer-focused strategy need customer accounting (CA) metrics. Yet accounting literature provides limited insights into what CA metrics are used, how they are used, or what factors influence CA measure choice or hinder more widespread adoption of CA practices. This thesis enhances knowledge of actual CA practices as they operate in firms with a customer-focused strategy and uses contingency theory to explain the choice of CA practices and their use in three exploratory case studies consisting of two national banks and a global courier company. The two strategic business units in Alphabank employ locally-developed, activity-based costing systems to produce CA information. Personal Banking incorporates a ‘customer needs met’ variable into a customer lifetime value measure used to segment customers based on potential profitability. Business Banking is smaller and currently uses historical customer profitability analysis at the individual customer level. Despite Alphabank’s overall customer-focused strategy, only product profitability is reported at executive level, and tensions between finance and operations potentially hinder more widespread CA usage. Betabank offers excellent customer service, but despite being very customer-focused they do not measure customer profitability. Executives use predominantly aggregate financial figures with a focus on net interest margin. Service excellence is paramount and Betabank do not consider financial CA useful as they do not segment customers. However, they extensively use non-financial customer related measures to monitor excellent customer service provision in order to enhance future profitability. The courier company uses activity-based costing to produce historical customer profitability analysis which reports direct margin, gross margin and earnings before interest and tax. The analysis discloses significant profitability differences between customer segments, and even between individual customers within segments where customer relationship management is employed. They do not measure full customer lifetime value but the next year’s customer profitability can be modelled using historical cost drivers. Financial CA measures drive initiatives to enhance customer profitability and/or trigger price negotiations. Non-financial CA measures are used to drive the customer-focused strategy and enhance profitability. The three cases demonstrate a considerable diversity in their usage of financial CA practices, with Betabank choosing to use no financial CA at all. Competitive intensity and the use of customer relationship management are found to be key drivers of CA usage at the individual customer level. Segmental customer profitability analysis is used when a large number of customers receive standard services at standard prices. No individual customer profitability analysis is needed for such homogenous customers as they can be efficiently managed using revenue. Non-financial CA measures were found to be widely used and hence a key contribution of this study is that in practice customer-related, non-financial performance measures are a key component of CA practices and may be extensively used to drive a customer-focused strategy. From case analysis a contingency-based framework has been develop which identifies combinations of factors with strong interrelationships and common influences on the choice and usage of CA measures. This framework provides three main groupings of contingent factors (type of competitive advantage, level of customer heterogeneity, and stage of organisational development) which together potentially have strong predictive power in relation to the nature of CA measures which benefit firms with a customer-focused strategy.
Keywords: Bank; Courier; Customer Accounting; Customer Profitability Analysis

Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.

Contracts as regulation model : applications and legal implications in over-the-counter financial markets - Borowicz, Maciej Konrad (European University Institute, 2016)
We develop a conceptual model of contracts as regulatory instruments in over-the-counter (OTC) financial markets. The model is informed by the functional understanding of financial regulation as addressing problems of counterparty risk, liquidity, information and systemic risk and structural understanding of regulation as a process of standard-setting, monitoring and enforcement. The justification of conceptualization contracts as regulatory instruments is found in the nature of the political economy considerations that inform the definition of certain contracts used in OTC financial markets. While many scholars rely on conceptualization of the said contracts as boilerplate, we argue that there exist important qualitative differences between boilerplate and regulatory contracts, which we link to a broader spectrum of interests taken into account in their definition in the process of standard-setting. The model and its application to loan and derivatives markets help to highlight the impact of governance features of the organization developing the contract and the regulatory competition to which the organization is exposed on the scope of the regulatory function. We also use a number of indicators and attributions to examine the effectiveness of regulatory contracts. While the contractual model displays some weaknesses in terms of both standard-setting (conflicts of interest) and enforcement (reliance on delegation) compared to its better established counterpart – the organizational model associated with exchanges – the contractual model helps to account for important self-regulatory features of OTC financial markets and offers suggestions as to how the structure of OTC financial markets can be improved.
Accepted: 2016-06-21T15:10:25Z
Keywords: Derivative securities; Financial risk management; Over-the-counter markets

The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation